One out of every three adult TB patients suffered from undernutrition in conflict affected Southern Ethiopia: a multicenter facility-based cross-sectional study - Abraham, Awoke; Yakob, Tagese; Dawit, Desalegn; Ashiko, Adisu; Tekese, Daniel; Israell, Eskinder (Frontiers in Epidemiology, 2025)
BackgroundAlthough tuberculosis mortality has dramatically decreased over the last decade, tuberculosis remains the world's biggest cause of death. Conflict affected nations hold vast majority of malnourished people globally, where many people die each year of tuberculosis. With regard to the global burden of tuberculosis, Ethiopia ranks third in the African continent and seventh overall. But in the research arena, the severity of the issue is not as well understood. Therefore, the current study aimed to assess undernutrition and the determinant factors among adult TB-patients receiving treatment in public health facilities in conflict affected zones of Southern.MethodsA multicenter facility-based cross-sectional study was conducted from 27/08/2023–28/ 09/2023 among 414 randomly selected adult (age ≥18 years) TB-patients receiving treatment at public health facilities in conflict affected zones of Southern Ethiopia. An interviewer-administered questionnaire and anthropometric measurements were used to collect data from study participants after written informed consent provision. By using SPSS Version 25, bivariate and multivariable logistic regression models were employed to determine the factors related to nutritional status.ResultsOverall, 33.3% of study participants had undernutrition, with a [95% CI (28.8%–38.1%)]. Factors such as cigarette smoking [AOR = 2.02, 95% CI; 1.22, 3.34] chat chewing [AOR = 2.50, 95% CI; 1.59, 3.93] regular cheka drinking [AOR = 1.82; 95% CI, 1.22–2.71] and household food insecurity [AOR = 1.78, 95% CI; 1.19, 2.66] had significant association with undernutrition.ConclusionsThe results of this study show that undernutrition affects one in three adult TB patients. Lifestyle factors such as smoking and chewing, and dietary factors like cheka eating and household food security had significant association with undernutrition. In order to improve the quality of life for TB patients, it is imperative that all stakeholders should prioritize addressing the lifestyle and nutritional aspects that are essential to the effectiveness of TB control and prevention initiatives.